Uma arqueologia do conceito de langue no curso de linguística geral e no proposições para uma semiologia e uma linguística - Donatti, Silvério Guazzelli (2018)
The present research will be based on the work of the Archeology of knowledge of Michel Foucault, an analysis of two saussurians discursive formations, with a view to the apprehension of the relations involving the concept of langue present in the works that compose our corpus, namely: the Course of General Linguistics, organized and edited by Charles Bally and Albert Sechehaye in France in 1916, and the Propositions for a Semiology and a Linguistics, a materialistic proposal articulated by Carlos Henrique de Escobar in Brazil in 1973. Our hypothesis was denied of a possible mutual re-elaboration between both discursive formations, through the concept of langue, due to the incompatibilities in the base of the discursive events that surround the concept.